Nurses' experiences of the ethical values of home care nursing: A qualitative study - Masoume Arab; Mohsen Shahriari; Amir Keshavarzian; Abbas Abbaszadeh; Mahrokh Keshvari (Elsevier, 2022)
Objective: Considering the importance of out-of-hospital services, the emergence of home care nursing, and the need for an ethical framework in nursing practice, the present study aimed to explore the nurses' experience of ethical values of home care nursing. Methods: The data of the study was collected using face-to-face individual interviews. Through purposive sampling, 20 nurses who worked in the home care centers in four cities of Iran in 2020 were interviewed. They shared their experiences of the ethical values of home care nursing. Then, the interviews were analyzed based on the content analysis approach and using Graneheim and Lundman method. Results: In the present study, 416 codes were extracted. Merging these codes based on the similarity, seven main themes, and 16 sub-themes were extracted. The themes included perception of the professional identity, respect for the client's autonomy, respecting privacy, establishing human interaction, maintaining mutual safety, observance of justice, and cultural-religious competence. The sub-themes included responsibility, development of professional and inter-professional interactions, maintaining the professional status at home, providing the holistic artistic care, patient's privacy, nurse's privacy, and maintaining the confidentiality of information, respect for the client's choice, honestly informing, empathetic interaction, adjusting the power positions, client's safety, nurse's safety, establishing justice, respect for the religious beliefs at home and cultural sensitivity. Conclusion: The participants stated that due to entering the patient's privacy in the home care cases, the ethical values such as perception of the professional identity, privacy, family interactions' management, mutual security, and cultural-religious competence became doubly important compared to the hospital caring.